Evaluation of balance in patients with chronic obstructive pulmonary disease with practical tests. Issue 4 (18th December 2020) - Yazici, Onur; Ceylan, Emel; Demir Yazici, Senay; Tas Gulen, Sule
Abstract: Introduction: Patients with chronic obstructive pulmonary disease (COPD) have impaired balance and hence fall more frequently. Easy application of balance evaluation tests can prevent the loss of time in the outpatient clinic for patients with COPD. In this study, we aimed to compare the efficacy of Berg Balance Scale (BBS), a time‐consuming but a widely used test, with other easy‐to‐perform tests such as the Single Leg Stance (SLS), Five Repetition Sit to Stand (5STS), Four Step Square (FSST), and Timed Up and Go (TUG) tests. Methods: A total of 71 patients with COPD and 70 control subjects with matching demographic characteristics were included in the study. All patients undertook pulmonary function tests and their scores of 6‐min walk‐test (6MWT), modified Medical Research Council (mMRC) dyspnoea scale, COPD assessment questionnaire (CAT) and body mass index (B) were recorded. In addition, the severity of airway obstruction (O), the dyspnoea severity (D) and exercise capacity (E) (BODE) index scores were measured. All patients with COPD were classified into four groups, A to D, based on the GOLD 2017 criteria. All subjects undertook the BBS, SLS, 5STS, FSST and TUG tests. Results: Balance tests revealed increased balance impairment in patients with COPD in comparison with the control subjects ( P < .05). The BBS, SLS, FSST and TUG examinations suggested that balance impairment was frequent in Groups C and D patients with COPD ( P < .05). FSST and TUG had the highest correlation with BBS ( r = −.812 and −.842 and P < .001 and <.001, respectively). The results of FSST and TUG were the closest to those of BBS test. Conclusions: FSST and TUG tests can be applied for the assessment of bodily balance status among patients with COPD in outpatient clinics.